2022
DOI: 10.3389/fnbeh.2022.944890
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Binge-Like Eating of Unsweetened vs. Sweetened Chow Pellets in BALB/c Substrains

Abstract: Binge eating disorder (BED) is defined as chronic episodes of consuming large amounts of food in less than 2 h. Binge eating disorder poses a serious public health problem, as it increases the risk of obesity, type II diabetes, and heart disease. Binge eating is a highly heritable trait; however, its genetic basis remains largely unexplored. We employed a mouse model for binge eating that focused on identifying heritable differences between inbred substrains in acute and escalated intake of sucrose-sweetened p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This work also advances our ability to model persistence of binge eating using preclinical approaches. Recent work found that during a 1 day reexposure test after incubation of binge-like eating, mice consumed similar amounts or more palatable food compared to the last day of baseline tests, highlighting the potential to examine binge eating persistence (Sena et al, 2022). The current work expands on this finding by completing three cycles of incubation and reexposure to palatable food across multiple days to examine not only the amount of palatable food consumed, but the patterns of reemergence and persistence in palatable food intake.…”
Section: Discussionmentioning
confidence: 99%
“…This work also advances our ability to model persistence of binge eating using preclinical approaches. Recent work found that during a 1 day reexposure test after incubation of binge-like eating, mice consumed similar amounts or more palatable food compared to the last day of baseline tests, highlighting the potential to examine binge eating persistence (Sena et al, 2022). The current work expands on this finding by completing three cycles of incubation and reexposure to palatable food across multiple days to examine not only the amount of palatable food consumed, but the patterns of reemergence and persistence in palatable food intake.…”
Section: Discussionmentioning
confidence: 99%
“…This work also advances our ability to model persistence of BE using pre-clinical approaches. Recent work found that during a one day re-exposure test after incubation of binge-like eating, mice consumed similar amounts or more PF compared to the last day of baseline tests, highlighting the potential to examine BE persistence (Sena et al, 2022). The current work expands on this finding by completing three cycles of incubation and re-exposure to PF across multiple days to examine not only the amount of PF consumed, but the patterns of reemergence and persistence in PF intake.…”
Section: Discussionmentioning
confidence: 99%